1984
DOI: 10.1021/ja00337a049
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on non-heme iron monooxygenase catalysis: epoxidation, aldehyde formation and demethylation by the .omega.-hydroxylation system of Pseudomonas oleovorans

Abstract: In previous work we have established that the "w-hydroxylation" system of P. oleouorans readily converts terminal olefins to the corresponding 1,2-oxides and does so stereoselectively. We also demonstrated loss of olefin configuration during enzymatic epoxidation, a result inconsistent with a concerted epoxidation mechanism ( J . Am. Chem. SOC. 1977,99, 2017-2024. Since loss of olefin configuration is unprecedented for monooxygenase-catalyzed epoxidations, these studies have been confirmed with isolated enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 2 publications
(2 reference statements)
4
33
0
Order By: Relevance
“…However, recombinants containing pCom8-GPo1-alkB-W55S or pCom8-GPo1-alkB-W55C did not grow on C 14 or C 16 , even after induction with dicyclopropylketone and in the presence of 0.01% rhamnolipids or Triton X-100. In combination with the observation that we were not able to obtain substrate range mu- tants with GPo1, this result indicates that GPo1 and derived recombinants lack an uptake system for alkanes longer than C 13 . Mutagenesis of the M. tuberculosis H37Rv AH.…”
Section: Vol 187 2005 Alkane Hydroxylase Substrate Range Mutants 87mentioning
confidence: 72%
See 2 more Smart Citations
“…However, recombinants containing pCom8-GPo1-alkB-W55S or pCom8-GPo1-alkB-W55C did not grow on C 14 or C 16 , even after induction with dicyclopropylketone and in the presence of 0.01% rhamnolipids or Triton X-100. In combination with the observation that we were not able to obtain substrate range mu- tants with GPo1, this result indicates that GPo1 and derived recombinants lack an uptake system for alkanes longer than C 13 . Mutagenesis of the M. tuberculosis H37Rv AH.…”
Section: Vol 187 2005 Alkane Hydroxylase Substrate Range Mutants 87mentioning
confidence: 72%
“…Growth experiments using baffled Erlenmeyer flasks showed that P. putida GPo1 is able to grow well on alkanes ranging from C 6 to C 13 , with growth rates ranging from 0.49 h Ϫ1 (doubling time, 1.7 h) for C 6 to 0.018 h Ϫ1 (doubling time, 40 h) for C 13 (Table 2). Selection experiments to obtain mutants of P. putida GPo1 able to grow on alkanes longer than C 13 failed also in the presence of a gratuitous inducer of the alk genes, dicyclopropylketone (8), and/or biosurfactants to facilitate alkane uptake by the strain, such as rhamnolipids (0.01%) or Triton X-100 (0.1%), failed to facilitate alkane uptake by this strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.11 P. putida GPo1 is able to oxidize linear alkanes ranging from n-pentane to n-dodecane by virtue of the AlkB hydroxylase system [170] and can oxidize also butane and propane, even though the degradation rate is much slower [165]. In addition to the hydroxylation of aliphatic and alicyclic, the AlkB system has been shown to catalyze: oxidation of terminal alcohols to the corresponding aldehydes; demethylation of branched methyl ethers; sulfoxidation of thioethers, and epoxidation of terminal olefins [171][172][173]. Methane, ethane, or alkanes longer than C 13 are not oxidized.…”
mentioning
confidence: 99%
“…The unsaturated aldehyde has been synthesized in widely different scales and diverse purposes, by dihydroxylation of one of the double bonds of 1,8-nonadiene, followed by oxidative fission of the resulting diol, 7,8 as well as by partial hydroboration-oxidation and further oxidation of 1,7-octadiene 9 and biochemical oxidation of this diene with Pseudomonas oleovorans monooxygenase. 10 Also, copper (I) and lead (IV)-catalyzed oxidative ring opening of cyclooctanol 11 were employed for its synthesis, as well as copper (I)-assisted conjugate addition of 4-pentenylmagnesium bromide to acrolein diethyl acetal, followed by acid hydrolysis of the resulting enol ether, 12 isomerization of cyclooctene oxide employing solid acids and bases, 13 and isomerization of 2,7-octadien-1-ol on copper, chromium and zinc composite catalysts at 180-250 ºC 14 or on a copper catalyst. 15 However, these approaches are not exempt from serious drawbacks, such as low yields, 7 use of harsh conditions, 13,14 requirement of expensive starting materials, 7,10,12 use of special or not readily available catalysts or co-factors, 10 inconvenient separation conditions, 14 such as preparative HPLC, 7 and the concomitant production of unwanted byproducts, 13 sometimes the aldehyde 8 being only a minor product.…”
mentioning
confidence: 99%